2014
DOI: 10.1111/all.12446
|View full text |Cite
|
Sign up to set email alerts
|

Group 2 innate lymphoid cells and CD4+ T cells cooperate to mediate type 2 immune response in mice

Abstract: Background Innate lymphoid cells (ILCs) play important roles in innate immunity and tissue remodeling via production of various cytokines and growth factors. Group 2 ILCs (ILC2s) were recently shown to mediate the immune pathology of asthma even without adaptive immunity. However, little is known about possible interactions between ILC2s and other immune cells. We sought to investigate the capacity of ILC2s to regulate effector functions of T cells. Methods We isolated ILC2s from the lungs of naïve mice. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
171
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(178 citation statements)
references
References 28 publications
7
171
0
Order By: Relevance
“…ILC2s were shown to have the capacity to enhance differentiation of naive CD4 + T cells to a Th2 phenotype while inhibiting Th1 differentiation in a contactdependent manner [16,17]. Together with analyses in helminth infection models showing that Th2 responses are impaired in the absence of ILC2s [18,19], these findings support a model in which ILC2s are "early sentinel" cells that can be rapidly activated to connect innate and adaptive immunity by acting as an early innate source of type 2 cytokines.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…ILC2s were shown to have the capacity to enhance differentiation of naive CD4 + T cells to a Th2 phenotype while inhibiting Th1 differentiation in a contactdependent manner [16,17]. Together with analyses in helminth infection models showing that Th2 responses are impaired in the absence of ILC2s [18,19], these findings support a model in which ILC2s are "early sentinel" cells that can be rapidly activated to connect innate and adaptive immunity by acting as an early innate source of type 2 cytokines.…”
Section: Introductionmentioning
confidence: 53%
“…The ability for ILC2 to produce IL-5 and IL-13 is drastically reduced in HDM-sensitized and -challenged Il21r −/− mice, although this is not a cell-intrinsic feature, thus suggesting that IL-21 may indirectly promote ILC2s [22]. OX40-L has also been implicated in the interaction between ILC2s and T cells [17] and more recently, it was shown that ICOS:ICOS-L interaction is critical for ILC2 function through STAT5 signaling, suggesting a possible role for B cells in the maintenance of ILC2s [39]. Our study however, indicates that B cells were dispensable for the initiation of ILC2 recruitment and their proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent papers have demonstrated that ILC2s are important in building a bridge between innate and adaptive immune responses, notably through MHC (major histocompatibility complex) class II interaction and antigen presentation 28,40,41 . However, in spite of the demonstration that T cells could maintain ILC2s to mediate the expulsion of Nb from the gut 10 days post infection 15 , it remained unclear whether the ILC2s could play a role in an anamnestic response.…”
Section: Discussionmentioning
confidence: 99%
“…However, as they express CD45 and are dependent on traditional T cell growth factor signaling pathways such as those mediated through the common γc-chain and IL-7 receptor-a chain (CD127), they have been called innate lymphoid cells. Numerous murine studies have now shown that ILC2-driven type 2 cytokine production is sufficient to induce allergen-mediated airway inflammation (Drake et al, 2014) and viral infection-induced AHR (Chang et al, 2011) in the absence of conventional T cells. The effects of these ILC2s on allergic inflammation are thought to be IL-13-mediated as adoptive transfer of wild-type ILC2s producing IL-13, but not IL-13 −/− cells, into IL-13-deficient mice was shown to be sufficient to induce allergic inflammation (Barlow et al, 2012).…”
Section: Lessons Learned From Mouse Models Of Asthmamentioning
confidence: 99%